AN EXPLORATORY STUDY OF HUMAN RESOURCE DEVELOPMENT PRACTICES IN TELECOM INDUSTRY IN SAUDI ARABIA: A CASE STUDY OF PRIVATE SECTOR - Al-Kahtani, Nasser S.; Ali Khan, Nawab (European Scientific Journal, ESJ, 2014)
The telecom sector of Saudi Arabia holds the largest position in the entire Middle East. After staying dormant until 2000, the telecom sector recorded supernormal growth in the past decade, thanks largely to liberalization of the sector since 2003. Today, the sector is highly competitive, with private players vying for market share by aggressively cutting tariffs—in fact, this has been the trend for five years now.The reason for which Saudi Arabia is so attractive to all the telecom operators is the combination of its population size and wealth. The growing importance of this sector has attracted the attention of the Researchers in the present research paper is to make an empirical study of private sector telecom industry regarding the HRD practices. The case study selected by the Researchers is of Mobily Telecom Company. A survey questionnaire has been constructed and administered among the employees of Mobily at managerial and non-managerial level from the selected districts of regions of Saudi Arabia. The Sample of the study has been undertaken of 85 employees. The study brings out the existing picture of HRD practices in Private Sector Telecom Company and offers suggestions to improve the pace of such practices wherever they need improvement.